Design and analysis of microstrip patch antenna for 5G wireless communication systems - Md. Sohel Rana; Md. Mostafizur Rahman Smieee (Institute of Advanced Engineering and Science, 2022)
Due to lower latency, greater transmission speed, wider bandwidth, and the possibility to connect with greater multiple devices, fifth-generation (5G) networks are far better than 4G. In this study, a microstrip patch antenna operating at 28 GHz is investigated and modeled for future 5G communication technologies. The substrate used in this work for the antenna is Rogers RT/Duroid5880. Dielectric of the substrate is 2.2 and thickness is 0.3451 mm. CST software is used to simulate the antenna as it is convenient to use. From the simulation, the return loss, gain, radiation efficiency, side-lobe level was found to be -38.348 dB, 8.198dB, 77%, and -18.3 dB respectively. The result found from this simulation is better than the works took place in the past. As a result, it can be utilized as a capable candidate for 5G wireless technology. The results of this proposed antenna are superior to those of existing antennas published in recent scientific journals. As a result, it's likely that this antenna will meet the needs of 5G wireless communication systems.